158 Long-Term Safety of Deutetrabenazine for the Treatment of Tardive Dyskinesia: Results From an Open-Label, Long-Term Study. (15th June 2018) - Anderson, Karen E.; Davis, Mat D.; Factor, Stewart A.; Hauser, Robert A.; Jarskog, L. Fredrik; Jimenez-Shahed, Joohi; Kumar, Rajeev; Ochudlo, Stanislaw; Ondo, William G.; Fernandez, Hubert H.
Abstract: Introduction: In the 12-week ARM-TD and AIM-TD studies, deutetrabenazine showed clinically significant improvements in Abnormal Involuntary Movement Scale (AIMS) scores at Week 12 compared with placebo, and was generally well tolerated. Objective: To evaluate the long-term safety/tolerability and efficacy of deutetrabenazine in patients with TD. Week 54 open-labelresults are reported in this interim analysis. Methods: Patients with TD who completed ARM-TD or AIM-TD were included in this open-label, single-arm extension study, in which all patients restarted/started deutetrabenazine 12 mg/day, titrating up to a maximum total daily dose of 48 mg/day based on dyskinesia control and tolerability. The study comprised a 6-week titration period and a long-term maintenance phase. Safetymeasures included incidence of adverse events (AEs), serious AEs (SAEs), drug-related AEs, and AEs leading to withdrawal, dose reduction, or dose suspension. This analysis reports results up to Week 54. Results: 304 patients enrolled in the extension study. There were 215 patient-years of exposure in this analysis, and exposure-adjusted incidence rates (EAIRs) of AEs (incidence/patient-years) were comparable to or lower than those observed with short-term deutetrabenazine treatment and placebo. The frequency of SAEs (EAIR 0.14) was similar to rates observed with short-termplacebo (EAIR 0.33) and deutetrabenazine (EAIR range 0.06–0.33) treatment. AEs leading to study discontinuation (EAIR 0.08), dose reduction (EAIR 0.17), and dose suspension (EAIR 0.09) were uncommon. Conclusions: Long-term treatment with deutetrabenazine was generally safe and well tolerated in patients with TD, and did not result in cumulative toxicity. Presented at: The American Psychiatric Association 2017 Annual Meeting; May 20–24, 2017; San Diego, California, USA. Funding Acknowledgements: This study was funded by Teva Pharmaceutical Industries, Petach Tikva, Israel.